Competencias complejas para la formación directiva (2016)
This paper describes the organizational complexity theory. We review the different concepts and applications of complexity in the organization, presenting the theories of complex systems, which have modernized the development of business activities, taking into account human interactions, and social interactions of organizations. It seeks to understand chaos theory and complexity made by Edgar Morin, for the evolution of organizations, analyzing the synergy of the organizational structure with the individual and the environment, coming to identify the concepts that help the organization operate within its organizational system, order, synergy, structure, efficiency, and stability strategy.